Stabilisation of the Regional Economy in Wartime: Lessons from Past Experiences and Adaptation Strategies - Khymych, Oksana; Ahieieva, Iryna; Klimova, Inna; Химич, Оксана Володимирівна; Агєєва, Ірина Вікторівна; Клімова, Інна Олександрівна (Poland : Futurity Research Publishing, 2024)
EN: The article researshes indicators of the development of the economy of Ukraine for the period 2019-2023. The problems that have a negative impact on the economy of Ukraine, caused by full-scale military aggression, have been researched. The article consolidates anti-crisis measures aimed at stabilizing the regional economy in war conditions, taking into account the positive results of the experience of previous periods. The work offers means of retraining labor resources and ways to solve problems related to the shortage of personnel. /// UA: У статті розглядаються індикатори розвитку економіки України за період 2019-2023 років. Проблеми, які негативно впливають на економіку України через повномасштабну військову агресію, були досліджені. Стаття консолідує антикризові заходи, спрямовані на стабілізацію регіональної економіки в умовах війни, враховуючи позитивні результати досвіду попередніх періодів. Ця робота пропонує можливості перепідготовки робочих ресурсів і шляхи вирішення проблем, пов'язаних із нестачею кадрів.
Стабілізація регіональної економіки у воєнний час: уроки минулого досвіду та стратегії адаптації
Keywords: economic stability; crisis management; regional strategies; economic recovery; adaptation measures; економічна стабільність; антикризове управління; регіональні стратегії; економічне відновлення; адаптаційні заходи